Modern possibilities of correcting violations of the vaginal biotope in pregnant women at risk in wartime conditions - I.A. Zhabchenko; V.K. Lihachov; I.S. Lishchenko; O.M. Bondarenko; T.M. Kovalenko (Publishing House TRILIST, 2023)
Research objective: to determine the effectiveness of a complex local preparation with antiseptic action based on octenidine and repair agent dexpanthenol (Prodexyn) in the syndrome of abnormal vaginal discharge (AVD) in pregnant women with obstetric pathology during the gestation and in the sanitation of the birth canal on the eve of childbirth. Materials and methods. 49 pregnant women were examined and divided into 2 groups: group I - 21 women (including 6 pregnant women with the status of internally displaced persons (IDPs)) with AVD in the period of 14-36 weeks of pregnancy; group II - 28 pregnant women (15 of them IDPs) on the eve of childbirth, who needed sanitation of the birth canal in the period of 37-41 weeks. The selection of patients was based on complaints, objective examination in mirrors and determination of vaginal pH. A bacterioscopic and bacteriological study was carried out if the pH deviates from the norm in order to identify pathogens and control the treatment effectiveness. Prodexyn was prescribed to all women in the vaginal suppositories at night for 10 days from the II trimester of pregnancy. Results. Most of women had a complicated obstetric and gynecological history, chronic inflammatory diseases of the pelvic organs, and viral infections. 87.7% of women had obstetric complications during current pregnancy. In the group I the primary average value of vaginal pH was 4.94 ± 0.02, and was the highest in IDPs (5.0-5.3). In the group II the pH before delivery at the initial screening was 5.1 ± 0.03, and in IDPs it was 5.7. Bacterioscopic examination in both groups showed a large number of leukocytes, cocci and fungal flora. Bacteriological examination in both groups showed a total of 11 pathogenic and opportunistic pathogens in various 2-3 component microbial and microbial-fungal associations against the background of a significant decrease in the number of lactobacilli. Single cases of Staphylococcus aureus and Streptococcus agalactiae (in group I) and Streptococcus viridans (in group II) were found. After sanitation the state of the vaginal biotope significantly improved in the majority of pregnant women of both groups. pH in group I was 4.51 ± 0.013, in group II was 4.55 ± 0.03. According to bacterioscopy, the number of leukocytes, coccal, bacillus and fungal flora significantly decreased in both groups. Bacteriological examination showed positive dynamics of the microflora concentration and the amount of its species spectrum. The lactobacilli concentration increased in both groups. Worse indicators of the vaginal biotope restoration were observed in IDPs, especially in the I group in the II-III trimesters, which required an extension of the treatment course for another 5-10 days. Conclusions. The complex local preparation with antiseptic action Prodexyn for AVD in pregnant women with obstetric pathology has shown its effectiveness and safety. As a result of the treatment, the number of pathogenic and conditionally pathogenic flora decreased significantly, with a simultaneous increase in the saprophytic flora and lacISSN 2309-4117tobacilli concentration.